The nexus of localism on company performance in the modest fashion business in Indonesia - Munawaroh, Munawaroh; Rusfian, Effy Zalfiana; Indriati, Fibria (International Journal of Innovative Research and Scientific Studies, 2025)
The growth of global Muslim consumer spending on halal-related commodities has significantly increased, with modest fashion emerging as a notable sector. Despite Indonesia's substantial Muslim population, the country remains a market rather than a leader in modest fashion exports, ranking ninth in exports to OIC countries. This study investigates how fashion localism—focusing on local production and cultural elements—affects company performance in Indonesia's modest fashion business. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), the research explores the impact of perceptions and behaviors related to design, raw materials, land ethics, employee development, consumer engagement, regulations, future opportunities, community development, and promotion. The findings reveal that all these factors have a significant and positive influence on company performance. Specifically, perceptions of design and raw materials, as well as behaviors related to employee development and consumer engagement, strongly impact company outcomes. The study underscores the importance of incorporating fashion localism strategies, including effective promotional tactics and regulatory adaptation, to boost competitiveness and performance in the modest fashion sector. This research provides valuable insights for business stakeholders aiming to leverage local strengths and cultural elements to enhance market positioning and overall performance.